KEPUTUSAN KONSUMEN DALAM MEMBELI PERUMAHAN (Sekolah Tinggi Ilmu Ekonomi Atma Bhakti, 2010)
Target of this research : to analyse influence of is quality of building, price, location, and promotion to decision of consumer in buying housing. Research population is housing consumer various type in Town region of Surakarta, sampel taken by counted 100 consumer. Technique intake of sampel with sampling purposive. Data collecting with questioner. Data analysis use analysis equation of regresi. Hypothesis tested with test of t test and F. Result of analysis indicate that the quality of building, price, location, and promotion have influence which are positive significance to decision of consumer. According to conclusion above its suggestion to: Relating to the quality of building, to government suggested to specify standard of quality of competent building to be dwelt. So that if there is developer developing house with quality of less competent can be acted and abstracted its effort permission. Government shall remain to give subsidy to housing consumer with small type and medium type to be society can occupy house with condition of better